Simulation-Based Mastery Learning Improves the Performance of Donning and Doffing of Personal Protective Equipment by Medical Students - Miller, Danielle; Pokrajac, Nicholas; Ngo, Jessica; Gallegos, Moises; Dixon, William; Roszczynialski, Kelly; Ng, Kristen; Taleghani, Nounou; Gisondi, Michael (The western journal of emergency medicine, 2022)
Introduction: Medical students lack adequate training on how to correctly don and doff personal protective equipment (PPE). Simulation-based mastery learning (SBML) is an effective technique for procedural education. The aim of this study was to determine whether SBML improves proper PPE donning and doffing by medical students. Methods: This was a prospective, pre-test/post-test study of 155 medical students on demonstration of correct PPE use before and after a SBML intervention. Subjects completed standard hospital training by viewing a US Centers for Disease Control and Prevention training video on proper PPE use prior to the intervention. They then participated in a SBML training session that included baseline testing, deliberate practice with expert feedback, and post-testing until mastery was achieved. Students were assessed using a previously developed 21-item checklist on donning and doffing PPE with a minimum passing standard (MPS) of 21/21 items. We analyzed differences between pre-test and post-test scores using paired t-tests. Students at preclinical and clinical levels of training were compared with an independent t-test. Results: Two participants (1.3%) met the MPS on pre-test. Of the remaining 153 subjects who participated in the intervention, 151 (98.7%) reached mastery. Comparison of mean scores from pre-test to final post-test significantly improved from an average raw score of 12.55/21 (standard deviation [SD] = 2.86), to 21/21(SD = 0), t(150) = 36.3, P <0.001. There was no difference between pre-test scores of pre-clinical and clinical students. Conclusion: Simulation-based mastery learning improves medical student performance in PPE donning and doffing in a simulated environment. This approach standardizes PPE training for students in advance of clinical experiences.